Finite Element Analysis of Reinforcement Design in Takeup Tower Under Dynamic Loading Conditions - Praja Dilla Atos; Romli, Romli; Nanda Yusril Mahendra; Agung Mataram; Amrifan Saladin Mohruni (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This research focuses on the finite element analysis for the design of reinforcement towers under dynamic load conditions. The reinforcement tower is a crucial part of the retrieval system that supports the system’s optimal function. This study identifies critical areas and plans reinforcement design steps on the construction of the retrieval tower. Stress analysis helps determine reinforcement design steps based on established standards and analytical approaches. The finite element method is used to analyze the design of the retrieval tower. The model is meshed into small triangular parts to find solutions in the form of finite element analysis of reinforcement tower design under dynamic load conditions. The results of finite element computation show normal stress fluctuations and increased displacement over time, indicating material deformation. This analysis is essential for understanding material behavior and designing systems that can effectively withstand dynamic loads.